ANAEROBIC ENDURANCE IN YOUNG FEMALE HANDBALL ATHLETES - Emanoel Vidal Soares, Pedro; Moreno Alves, Samuel; Rosa dos Santos, Lucas; de Souza Paula, Erick; de Freitas Pimenta Alves, Marcelle; Vitor Silva Martins, Magdiel; Rodrigo de Oliveira Silva, Pablo (Health and Society, 2024)
Introduction: Handball is a team sport with intermittent characteristics, alternating high intensity stimuli with periods of low intensity. Handball is characterized by an aerobic predominance, but it is anaerobic stimuli that determine the actions of the game. As several anaerobic actions are performed during the game, understanding the resistance of this metabolism in athletes becomes important. Objective: To compare the variables of anaerobic resistance in young players from different handball positions. Materials and methods: twenty female players with an average age of 16.8± 0.8 years participated in this study. The Running Anaerobic Sprint Test (RAST) was performed, which consisted of 6 sprints of 35 meters of running. Maximum, average and minimum power (absolute and relative) and fatigue index were calculated. Statistics with mean, standard deviation were used. To compare the different groups, ANOVA was used. Results: It was possible to observe values without significant statistical differences between the athletes in absolute power. In relative powers, it was possible to verify that point guards and wingers had higher values than goalkeepers and pivots (p<0.05). In relation to the fatigue index, wingers and point guards had lower values than goalkeepers and pivots (p<0.05). Conclusion: both in terms of power and fatigue index, point guards and wingers have better anaerobic conditioning than strikers and pivots. And pivots have better anaerobic capacity than goalkeepers. Further research on this topic is suggested to further consolidate the subject.